2018
DOI: 10.1177/1466138117728738
|View full text |Cite
|
Sign up to set email alerts
|

It makes you make the time: ‘Obligatory’ leisure, work intensification and allotment gardening

Abstract: This ethnographic study of busy allotment-holders explores the juxtaposition of time spent on the allotment with paid employment and caregiving. Highlighting the recent surge in allotment demand among professionals such as nurses and educators, the article examines the seeming contradiction of adding a very time-consuming responsibility onto an already packed schedule. It shows how the allotment's normative structure creates a sense of obligation, helping busy professionals make the time to explore what most p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
0
7
0
3
Order By: Relevance
“…Such findings are noteworthy in that gardeners' emotional feelings and experiences while gardening are important factors keeping them involved in gardening. Previous studies have revealed that long-term gardeners expressed more positive emotional benefits (happiness, enjoyment) resulting from community garden participation [41,64]. Further, other studies have found that emotional aspects, such as strong attachment toward gardens, played a role in influencing garden participation [21].…”
Section: Significant Effect Of Past Gardening Experience On the Assocmentioning
confidence: 98%
“…Such findings are noteworthy in that gardeners' emotional feelings and experiences while gardening are important factors keeping them involved in gardening. Previous studies have revealed that long-term gardeners expressed more positive emotional benefits (happiness, enjoyment) resulting from community garden participation [41,64]. Further, other studies have found that emotional aspects, such as strong attachment toward gardens, played a role in influencing garden participation [21].…”
Section: Significant Effect Of Past Gardening Experience On the Assocmentioning
confidence: 98%
“…The bureaucratic, outreach and organisational responsibilities were often an addition to the demands of paid work or study obligations, with a new coordinator noticing how the return to work after furlough impacted on their time and energy available for garden responsibilities. The work-life balance for community garden leaders apparently contrasts with those of allotment holders assessed by Schoneboom ( 2018 ). While Schoneboom ( 2018 ) argued that the demands of allotments are constructive in forcing people to make leisure time to counter the intensification and extensification of work into personal time, in this case, the type of tasks involved were an addition to work rather than a counter to it.…”
Section: Resultsmentioning
confidence: 76%
“…Schoneboom ( 2018 ) examined the interactions between allotment maintenance and employment workload on the wellbeing of those in full-time employment. This was based on the recognition of the increasing encroachment of work into personal life, which arguably has become considerably stronger since the normalisation of working from home during lockdown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, there is an extensive literature on the well-being gains that encounters with nature offer to time-poor or stressed workers. Existing studies point to the mental and physical health benefits that accrue to employees who are able have such encounters (Largo-Wight et al, 2017; Lottrup et al, 2015) and explore how time feels for busy professionals on their allotments (Schoneboom, 2018). Similarly, scholarship on the benefits of gardening for retired (and therefore relatively time-rich) people, shows a strong association between gardening and improvements in wellness (Hawkins et al, 2013; Milligan et al, 2004).…”
Section: The Radical Content Of Garden Timementioning
confidence: 99%